On the new model of funding and quality assurance of dermatovenereologic care - A. A. Martynov; N. N. Stadchenko; A. V. Vlasova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article deals with modern approaches to organization of delivery and financial support of high-tech medical care on the profile of "dermatovenereology", and with introduced mechanisms for quality assurance of medical care and independent evaluation of the services provided.